O papel do sindicato rural no enfrentamento da violência doméstica e sexual contra mulheres - Barbosa, Angela Silva (2023)
This dissertation analyzes the relevance of women's actions in front of the Union of Rural Workers and Workers (STR), in the municipality of Queimadas - PB, in the fight Against domestic and sexual violence against women residing in the rural area of the municipality. This research is developed in a qualitative way, seeking to cover bibliographical research, documental and field research, through interviews. In this one, we are registering and analyzing the actions that envision the empowerment of women linked to the STR and how access to public policies to face it happens, the assistance to domestic and sexual violence against women, and if this contributes to breaking the cycle of violence experienced by women in the rural area of Queimadas. We analyze how the STR dialogues about gender inequalities and women's rights. Thus, this work deals with the participation of women in rural unions as agents of social transformation in facing domestic and sexual violence against women.